Meaning is Use: the Case of Propositional Identity - Kupś, Leonard; Chlebowski, Szymon (Bulletin of the Section of Logic, 2024)
We study natural deduction systems for a fragment of intuitionistic logic with propositional identity from the point of view of proof-theoretic semantics. We argue that the identity connective is a natural operator to be treated under the elimination rules as basic approach.